Nutritional Status of Under-Five Children in the Climate Vulnerable Area of Bangladesh - Rahman, Sonia; Shafiqul Halim, Kazi; Kumar Banik, Protik; Tasnim Muna, Atiya; Khan, Bushra E Zannat; Jahrina, Rashna (Bangladesh Medical Journal, 2024)
Children, due to their physiological and metabolic vulnerabilities, are particularly sensitive to climate-related changes. Factors such as heat waves, extreme weather events, temperature variations, increased precipitation, and drought directly impact food and nutrition. This cross-sectional study was aimed to assess the nutritional status of under-5 children in a flood-prone district in northern Bangladesh. A total of 207 children aged 24-59 months were conveniently selected for the study. Data collection involved face-to-face interviews and observations using a semi-structured questionnaire. Data analysis was performed using SPSS version 16.0. Demographic information, educational background, immunization status, breastfeeding practices, health history, and dietary intake were considered for assessing nutritional status. More than half (55.6%) of the children was in age group 48-59 months, and the male-female ratio was 1.25:1. Most of the (70%) children belonged to nuclear families and more female children (53.6%) had completed their primary education than male (44%). All children were immunized, where three-fifth (60.4%) of the mothers acknowledged breastfeeding after birth, and three-fourth (75.4%) had completed exclusive breastfeeding. The majority were not ill in the month preceding the data collection. Dietary assessment revealed that most of the (94%) children consumed rice in the morning as breakfast, 97% at midday as lunch, and 94% at night as dinner. Among the children all of them had experienced flooding (100%) and significant proportion had experienced river bank erosion (97.6%). According to measurements, 81.2% were normal by MUAC, 62.8% by height for age Z scores, 71% by weight for age Z scores, and 83.1% by weight for height Z scores. The study identified higher proportions of underweight and severe wasted cases in male children, severe stunted cases with mothers having primary education, and severe wasted cases in extended families. Although certain trends were observed, the relationships between nutritional status and variables such as gender, maternal education, family type, and duration of residence were not statistically significant. Given the potential long-term impact of malnutrition, early intervention, and prioritization of nutritional considerations during the under-five age group are imperative. Bangladesh Med J. 2023 May; 52(2): 29-39